EFEKTIFITAS PENCATATAN KELAHIRAN BERDASARKAN UNDANG-UNDANG NO. 23 TAHUN 2006 (STUDI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KAB. GIANYAR) - I Komang Arya Andika Yasa; Ibrahim R.; I Ketut Suardita (Kertha Negara : Journal Ilmu Hukum, 2013)
In Gianyar regency Birth Registration performed at the Department of Civil and Population of Gianyar, the legal basic is Act No.23 of 2006. The problems is how does the implementation of birth registration in Gianyar regency, and what factors that influence the implementation of birth registration in gianyar. This research is empirical legal research with interview data collection techniques. The conclusion of this study show that the effectiveness of birth registration implemented under act number 23 of 2006 has not been implemented effectively it is mostly caused by the lack of infrastructure, lack of human resources community, broad of Gianyar district geographic factors, and weak law enforcement.